(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
“Torture is anguish queering in your chest, cold as ice and heavy as a stone, paralyzing as sleep and dark as the abyss. Torture is despair and fear and rage and hate. It is a desire to kill and destroy including yourself”.- Adriana P. Bartow1